2021
DOI: 10.1080/13825585.2021.1934387
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in cerebrovascular responses to cognitive stimulation using a novel method

Abstract: Aging is associated with a number of alterations to cerebrovascular function. We aimed to investigate the effect of age on cerebrovascular responses to cognitive stimulation using an objective twoparameter method.Previously derived from a large data-set (135 healthy participants) were applied to a task-activated dataset of 69 healthy participants in five different task conditions. Cumulative response rate (CRR) was calculated as the sum of responses across tasks and hemispheres.There was a significant effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(58 reference statements)
2
3
1
Order By: Relevance
“…Therefore, perhaps the age-dependent impairment of NVC is related to task complexity and vessel segment insonation, which might explain the notable disparity between studies. A recent study reported age-related increase in cerebrovascular response to cognitive stimulation ( 81 ), which differs to the outcome presented herein. The apparent discrepancy may point to differential outcomes dependent on task (stimulus) and selective cerebral vessels.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, perhaps the age-dependent impairment of NVC is related to task complexity and vessel segment insonation, which might explain the notable disparity between studies. A recent study reported age-related increase in cerebrovascular response to cognitive stimulation ( 81 ), which differs to the outcome presented herein. The apparent discrepancy may point to differential outcomes dependent on task (stimulus) and selective cerebral vessels.…”
Section: Discussioncontrasting
confidence: 99%
“…This is supported by data from Beishon et al. 73 who observed increased cerebrovascular velocity responses (∼44%) in the anterior circulation with advancing age to cognitive stimulation. This has also been documented in a review whereby Beishon et al.…”
Section: Discussionsupporting
confidence: 73%
“…72 Furthermore, studies using cognitive tasks provide support for elevated responses not representing a superior physiological response in the context of advancing age. This is supported by data from Beishon et al 73 who observed increased cerebrovascular velocity responses ($44%) in the anterior circulation with advancing age to cognitive stimulation. This has also been documented in a review whereby Beishon et al 6 highlighted individuals with mild cognitive impairment displayed elevated CBF responses to NVC tasks compared to healthy controls.…”
Section: Discussionsupporting
confidence: 64%
“…Compared to the more commonly used 95% confidence limit, the 90% threshold provided greater sensitivity, to the detriment of specificity, and a better yield. 42 For each task, a subject was classified as R if the response led to CCF/VR values greater than either CCF 90 ¼ 0.53 or VR 90 ¼ 2.59, as described previously. 21 Subjects not meeting these criteria were labelled as NoR, for the given cognitive task.…”
Section: Objective Criteria For Nvc Response Classificationmentioning
confidence: 99%
“…19 It is more likely that the changes of interaction between dCA and NVC in response to task activation might be as a result of age-related changes in cerebral vasomotion. 42,74 However, the reduction of ARI values due to mental activation is highly relevant to improve our understanding of dCA nonstationarity 75 with its inherent physiological variability, which might be the predominant cause of poor reproducibility 53,76 seen in task-activated studies. Thus, the BP-MCAv relationship may rapidly shift from the linear nature of dCA 77 at rest to nonlinear behaviour during neural stimulation, due to the interaction between myogenic and metabolic activities.…”
Section: Dca During Neural Stimulationmentioning
confidence: 99%